The Perception Towards the Quality of Work Life Among the Women Faculty Members of Arts and Science Colleges In Tiruchirappalli District - Vinoth Kumar (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
Women teachers in college play an important role in female empowerment particularly in education sector. Availability of women teachers, both in schools and colleges, brings a sense of security among girl students helping them to step out of their comfort zone. In colleges women teachers could be the best counsellors for the girl students. The objectives of the study are, To analyse the socio economic profile of the women faculty members in the arts and science colleges in the Tiruchirappalli District. To examine the perception towards the quality of work life among the women faculty members of arts and science colleges in Tiruchirappalli District. The research design used for this study is explorative and analytical. The aim is to obtain complete and accurate data. It is designed to provide a background to explore and analyse the Quality of Work Life of the Women Teachers in the Arts and Science Colleges. In this study majority 37 percent of the respondents form 31 – 40 years age category and only 16 percent of the respondents are in below 30 years age group. In this research majority 67.9 percent of the respondents are married and it is noted that 7.7 percent of the respondents come under divorced category. In this study, majority 37.8 percent of the respondents are from semi-urban areas, and 28.7 percent of the respondents from urban areas.